The Etiology and Prognosis of Delayed Postoperative Leukocytosis in Lung Transplant Recipients. (June 2020) - Izhakian, Shimon; Wasser, Walter G.; Vainshelboim, Baruch; Unterman, Avraham; Heching, Moshe; Gorelik, Oleg; Kramer, Mordechai R.
Background: Leukocytosis (white blood cell count >12 000/µL) in the delayed postoperative period (4-7 days) after lung transplantation is due to diverse etiologies. We aimed to describe the etiologies of delayed postoperative leukocytosis in lung transplant recipients and to evaluate the association of leukocytosis causes with short-term survival. Methods: A retrospective chart review of 274 lung transplantations performed in our institution during 2006 to 2013. Results: Delayed postoperative leukocytosis was seen in 159 (58.0%) of lung transplant recipients. In 57 (35.8%) of them, the etiology of the leukocytosis was not identified. The etiologies of leukocytosis that were identified were infection (n = 39), second surgery, acute rejection (n = 12), primary graft dysfunction (n = 3), multiple etiologies (n = 17), and other causes (n = 10). On multivariate analysis, delayed postoperative leukocytosis was one of the variables that most significantly associated with decreased survival in the entire sample (hazard ratio [HR] = 1.52, 95% confidence interval [CI]: 1.01-2.29, P = .040). On additional analysis for mortality assessing each leukocytosis subgroup, the data were acute graft rejection (HR = 8.21, 95% CI: 4.09-16.49, P < .001), second surgery (HR = 2.05, 95% CI: 1.08-3.90, P = .020), primary graft dysfunction (HR = 2.72, 95% CI: 0.65-11.33, P = .169), other causes (HR = 1.30, 95% CI: 0.47-3.62, P = .620), and unknown etiology (HR = 0.94, 95% CI: 0.54-1.62, P = .800). Conclusions: Delayed post-lung transplant leukocytosis is a poor prognostic sign, especially when attributed to acute graft rejection, infection, and multiple etiologies. In the absence of an identifiable etiology, it can be attributed to postoperative reactive stress, is not associated with increased mortality, and likely does not warrant further diagnostic investigation.